Presence of dysfunction and myocardial remodeling in patients with premature ventricular complex-induced cardiomyopathy - a cardiovascular MR study. (13th July 2021) - Kirchgaessner, N; Salatzki, J; Lugenbiel, P; Ochs, A; Hund, H; Katus, HA; Frey, N; Giannitsis, E; Friedrich, MG; Andre, F; Scholz, E; Ochs, MM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Premature ventricular complexes (PVCs) in the absence of underlying structural heart disease are considered to be benign. However, cardiac dysfunction has been observed in patients with a high PVC burden. The characterization of a PVC-induced cardiomyopathy with structural remodeling including myocardial fibrosis and the determination of a specific PVC burden leading to subclinical cardiac dysfunction remains to be determined. Objectives: We aimed to evaluate cardiac function, remodeling and myocardial fibrosis patterns in patients with PVCs using cardiac magnetic resonance imaging (CMR). Additionally, we aimed to determine a PVC cut-off value leading to subclinical cardiac dysfunction. Methods: Patients who underwent CMR and 24-hour, 12-lead ECG monitoring (Holter ECG) within six months were retrospectively studied. Patients with evidence of structural heart disease were excluded. The cohort was subdivided based on the number of PVCs in Holter ECG; Group-1 = 0-100, Group-2 = 100-5000 and Group-3 > 5000 PVCs. CMR parameters were extracted from our local databank. Myocardial strain was measured using feature tracking. For quantification of myocardial fibrosis, T1 mapping and late gadolinium enhancement (LGE) were investigated. Z-scores were calculated in order to combine T1 values from a 1.5 and 3Tesla CMR vendor. Results: 443 patients (52 ± 20 years, 45% females) were included in the study. Compared to Group-1, Group-3 revealed a significantly reduced LV-EF, an increased indexed LV-EDV and increased indexed LV-ESV, indicating cardiac dysfunction and LV enlargement. PVCs frequency was inversely correlated with LV-EF (r=-0.23, p < 0.001) and positively correlated with indexed LV-EDV (r = 0.13; p < 0.01). Feature tracking showed significantly higher global circumferential strain (GCS) indicating subclinical dysfunction. Global T1 times were significantly prolonged in Group-3. Elevated global T1 Z-scores were found in Group-2 and Group-3 compared to Group-1. Significantly more intramural LGE was present in Group-2. The PVC cut-off value characterized by reduced GCS was defined by 216 PVCs (AUC = 0.61, p = 0.02). Conclusion: CMR revealed cardiac dysfunction, left ventricular enlargement and diffuse myocardial fibrosis in patients with PVC in the absence of structural heart disease. These changes indicate the development of a PVC-induced cardiomyopathy depending on the PVC burden. Interestingly, subclinical myocardial dysfunction was determined at already low PVC frequencies. Further investigations are necessary in order to examine the influence of different origins of PVCs and the development of structural remodeling.